Polyelectrolyte complex based nanofibrous aggregates for fast hemostasis. (June 2021) - Hossain, Sabir; Mohanty, Sibanwita; Verma, Devendra
Abstract: Uncontrolled bleeding is the leading cause of death in military combat and the second leading cause of death in the civilian population. Many hemostatic agents have been developed. However, a bandage that is inexpensive, effective, and easy to use is not available yet. The current work is based on the development of nanofibrous polyelectrolyte complex (PEC) aggregates made of chitosan and alginate (ChAlg) and evaluating their biocompatibility and efficacy. Chitosan and alginate are complementary charged to each other and self-assemble at low pH into fibrous structures with an average fiber diameter below 100 nm. The dried PEC nanofibrous aggregates were characterized for their nano-structure, biocompatibility, and clotting efficiency. The clot strength depends on the amount of chitosan present in the PECs. PECs containing an equal ratio of chitosan and alginate have shown blood clotting time 15 ± 3 s & 42 ± 4 s in-vitro and in-vivo, respectively. The nanofibrous structure and high absorption capacity of the PECs appear to be the primary reason that facilitates faster clotting of the nanofibrous aggregates. Further in-vivo studies show that PEC fibers are safe and biocompatible.